The Existence of Muhammadiyah’s Islamic Education in Facing Generation Alpha and the Era Society 5.0 - Rofingah, Rofingah; Lailan Arqam, Muhammad (Universitas Ahmad Dahlan, 2024)
Generation Alpha and the era of society 5.0 are an obstacle for Muhammadiyah’s Islamic Education. Because everything is based on technology, all information is easy to get through digitally, which has positive and negative impacts. The negative effect is more dominant, so the progressivism of Muhammadiyah’s Islamic Education becomes necessary for education providers. The research aims to explore the existence of Muhammadiyah’s Islamic Education in facing the Alpha generation and the era of Society 5.0. In this study, the authors used a qualitative method of library research. Journals, articles, books, and other relevant information can support this article's data as a source. The results showed that the existence of Muhammadiyah’s Islamic Education in the generation Alpha and the era Society 5.0 was pursued by innovating technology-based learning and lecture programs such as the eduMu, edutabMu, ISMUBAKU and SiberMu University and Trensains schools.